Reduced Toll-Like Receptor 9 Expression on Peripheral C D14+ Monocytes of Chronic Hepatitis B Patients and its Restoration by Effective Therapy. Issue 7 (October 2014) - Huang, Yi-Wen; Hsu, Cheng-Kai; Lin, Shih-Chang; Wei, Shu-Chen; Hu, Jui-Ting; Chang, Han-Yu; Liang, Cher-Wei; Chen, Ding-Shinn; Chen, Pei-Jer; Hsu, Ping-Ning; Yang, Sien-Sing; Kao, Jia-Horng
Background: Chronic hepatitis B (CHB) patients display Toll-like receptor 9 (TLR9)-dependent defective immune responses. We aimed to study TLR9 expression on CHB patients and its alteration during therapy. Methods: We compared TLR9 expression on fresh peripheral CD14 + monocytes from a cohort of 97 CHB patients and 35 HBsAg-negative, anti-HCV-negative controls, during pegylated interferon or entecavir therapy. TLR9 expression on liver tissue was also investigated. Results: Compared with controls, peripheral CD14 + monocytes of CHB patients displayed reduced expression of TLR9 mean fluorescence intensity (MFI; 9.90 ±3.64 versus 7.95 ±3.61; P =0.007) independent of age, gender and alanine aminotransferase (ALT; -2.09, 95% CI -3.568, -0.613; P =0.006). Furthermore, age, gender, ALT, HBeAg status, quantitative HBsAg (qHBsAg) or HBV DNA did not predict the TLR9 expression ( P =0.863). Hepatic TLR9 messenger RNA (mRNA) was significantly reduced in 54 patients compared with 3 controls (0.45 ±0.32 versus 1-fold). Using response-guided therapy by qHBsAg levels and pretreatment TLR9 MFI as a reference, TLR9 MFI restored to a mean of 1.7- to 2.7-fold in pegylated interferon responders and reduced to a mean of 0.6-to 0.7-fold in non-responders starting from treatment week 12. Among 10 entecavir-treated patients, TLR9 MFI gradually restored to a mean of 1.2- to 2.1-fold starting from treatment week 48. Conclusions: CHB patients display reduced TLR9 expression on peripheral CD14 + monocytes, which is independent of host and viral markers, and on liver tissue. Responders to pegylated interferon and those under entecavir demonstrate restoration of TLR9 expression. On-treatment TLR9 expression on peripheral monocytes might predict response to pegylated interferon therapy.